Analisis Manajemen Persediaan Bahan Baku Pada Agroindustri Tahu “Lutfi” Di Kecamatan Siak Hulu Kabupaten Kampar Provinsi Riau - Dewi, Ilma Satriana; Marliati, Marliati; Fahrial, Fahrial (Jurnal Bisnis Tani, 2025)
Soybeans as a raw material for making tofu are generally supplied from foreign countries or imported. The reason is that the number of soybeans in the country is limited and the quality is not as good as soybeans from abroad. Raw materials need to be calculated so that the quantity is effective, if there is a shortage of raw materials it will result in reduced production quantities. On the other hand, if there is too much raw material inventory it will result in high costs. This research aims to analyze the optimal amount of raw material inventory, the total cost of raw material inventory, the amount of safety stock and reorder points in the Lutfi tofu agroindustry. This research method was carried out using a survey method for the case of the Tahu Lutfi agro-industry business. The research respondents were the Tahu Lutfi business owner as the main informant and 3 workers as respondents for additional information. Respondents were taken using census techniques. The analytical tools are EOQ (Economic Order Quantity), Total Inventory Cost, Safety Stock and Reorder Point Analysis. The results of the analysis for each objective are EOQ of 1,333.73 kg, total inventory costs per month of Rp 450.37. Safety stock results are 162 kg and Reorder Point is 408.66 kg.